Dental care to the oncological patient in terminality - Karina da Costa Lima SOUTO; Diego Belmiro do Nascimento SANTOS; Ully Dias Nascimento Távora CAVALCANTI (Faculdade São Leopoldo Mandic, 2019)
End-stage cancer patients present many oral manifestations that need the support of a dentist, who included in the multidisciplinary team, must make the necessary adjustments in order to maintain the quality of life of these patients relieving their pain and suffering. Based on a literature review, the research searched articles published between June 2000 and February 2019, in the following databases: Pubmed, Scielo, Lilacs, Wiley Online Libary. The following inclusion criteria was used: articles published in Portuguese or English which included the keywords: dental care, critical care, palliative care, terminally ill. The aim of this paper is to present the importance of dental care to patients with cancer in palliative care. In conclusion, it was possible to verify that Dentistry in the hospital environment is of paramount importance, and should be based on empathy and communication, seeking to create the necessary bonds for the development of an effective and individualized treatment plan, discussion of cases in an integrated way and demonstrating the importance of higher education institutions in the training of future professionals. This paper aims to be contributory in order to increase the discussion about palliative care in Dentistry, besides providing subsidies to future studies that will deepen in this essential and still unexplored subject.